FAKTOR-FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHING SECARA VOLUNTARY - R. Meike Erika Dwiyanti; Arifin Sabeni (Diponegoro Journal of Accounting, 2014)
This study aimed to examine the factors that affect the auditor switching voluntarily. Variables that considered to affect are management changing, qualified opinion, company size, audit quality, financial distress and audit fees.The populations in this study are all companies listed in Indonesia Stock Exchange, period 2008-2012. The methods used to determine sample is purposive sampling. The criteria are companies which switching auditor not due to regulation No. 17/PMK.01/2008 and firm serving the complete financial statements and accessible. Based on those criteria, 230 companies acquired during five years of observation.The analysis showed that change in management, qualified opinion, company size, audit quality and financial distress significantly influence auditor switching, while audit fee not.